Fostering the Reconstruction of Meaning Among the General Population During the COVID-19 Pandemic - Castiglioni, Marco; Gaj, Nicolo’ (Frontiers in Psychology, 2020)
The COVID-19 outbreak has seen people in many countries asked to radically modify their way of life in compliance with sweeping safety measures. During the current crisis, technology is turning out to be key, in that it allows practitioners to deliver psychological services to people who would otherwise be unreachable. However, professionals cannot solely rely on their traditional modes of practice, in that different methods are required to bring to light the needs of those affected by the emergency. People are being overwhelmed by a cascade of unusual and unexpected events that are putting a strain on their everyday routines and usual meaning-making systems; ongoing challenges to their employment and financial status will likely divert personal resources away from psychological well-being. We therefore argue that psychologists should also consider the needs of the general population. Among those who may require help – aside from the main targets of psychological intervention, such as healthcare personnel and COVID-19 patients and their relatives – specific attention should be paid to those who are not at the center of the crisis. We suggest that this large segment of potential users may benefit from a non-medical approach focused on the promotion of meaning-making processes. Indeed, the disruptive nature of the current situation hinders sense-making and threatens to undermine psychological balance and well-being, at an individual as well as at a societal level. The present article proposes a methodological perspective based on the reconstruction of meaning-making processes (sense of coherence, predictability, metaphors, narratives). Specifically, psychological interventions should promote personal and collective resources with a view to: “normalizing” current distressful experiences (i.e., acknowledging that such reactions are normal in light of the present situation); widening the observational field, taking relational contexts into account, and promoting an understanding of distressful experiences as coping strategies; fostering meaning-making/reconstruction processes through the use of appropriate metaphors and narratives; promoting a sense of coherence. We present two clinical vignettes to illustrate how these principles might be applied in practice. In conclusion, the exceptional psychological challenges posed by the COVID-19 pandemic require practitioners to adopt a broad and flexible perspective on clinical intervention.